Crystal structure of Trichinella spiralis calreticulin and the structural basis of its complement evasion mechanism involving C1q - Jia, Zhihui; Yu, Wen; Li, Jingmo; Zhang, Mingming; Zhan, Bin; Yan, Liming; Ming, Zhenhua; Cheng, Yuli; Tian, Xiaolin; Shao, Shuai; Huang, Jingjing; Zhu, Xinping (Frontiers in Immunology, 2024)
Helminths produce calreticulin (CRT) to immunomodulate the host immune system as a survival strategy. However, the structure of helminth-derived CRT and the structural basis of the immune evasion process remains unclarified. Previous study found that the tissue-dwelling helminth Trichinella spiralis produces calreticulin (TsCRT), which binds C1q to inhibit activation of the complement classical pathway. Here, we used x-ray crystallography to resolve the structure of truncated TsCRT (TsCRTΔ), the first structure of helminth-derived CRT. TsCRTΔ was observed to share the same binding region on C1q with IgG based on the structure and molecular docking, which explains the inhibitory effect of TsCRT on C1q-IgG–initiated classical complement activation. Based on the key residues in TsCRTΔ involved in the binding activity to C1q, a 24 amino acid peptide called PTsCRT was constructed that displayed strong C1q-binding activity and inhibited C1q-IgG–initiated classical complement activation. This study is the first to elucidate the structural basis of the role of TsCRT in immune evasion, providing an approach to develop helminth-derived bifunctional peptides as vaccine target to prevent parasite infections or as a therapeutic agent to treat complement-related autoimmune diseases.